Knowledge processing and data analysis first International Conference, KONT 2007, Novosibirsk, Russia, September 14-16, 2007 and first International Conference, KPP 2007,Darmstadt, Germany, September 28-30, 2007, revised selected papers - KONT 2007 (2007 Novosibirsk, Russia); Wolff, Karl Erich; Palchunov, Dmitry E.; Zagoruiko, Nikolay G.; Andelfinger, Urs.; SpringerLink (Online service). (Heidelberg New York Springer, 2011)
This book constitutes the proceedings of the First International Conference on Knowledge - Ontology - Theory (KONT 2007) held in Novosibirsk, Russia, in September 2007 and the First International Conference on Knowledge Processing in Practice (KPP 2007) held in Darmstadt, Germany, in September 2007. The 21 revised full papers were carefully reviewed and selected from numerous submissions and cover four main focus areas: applications of conceptual structures; concept based software; ontologies as conceptual structures; and data analysis.
Electronic reproduction.
Keywords: Expert systems (Computer science) -- Congresses; Artificial intelligence -- Congresses; Electronic books